Bacterial and Fungal Communities in Tempeh as Reveal by Amplified Ribosomal Intergenic Sequence Analysis - SEUMAHU, CECILIA ANNA; SUWANTO, ANTONIUS; RUSMANA, IMAN; SOLIHIN, DEDY DURYADI (Bogor Agricultural University, Indonesia, 2013)
Tempeh is an Indonesian traditional fermented food produced using Rhizopus as a starter culture. In practice, however, the starter culture as well as fermentation processes would yield a polymicrobial fermentation, which generated a unique tempeh flavor and texture. This condition makes Indonesian tempeh as one of the most complex fermented food, while at the same time would make it difficult to scale up tempeh production with uniform quality and consistency. The aim of this study was to compare a number of tempeh microbial communities employing Amplified Ribosomal Intergenic Sequence Analysis (ARISA). Fresh tempeh samples were obtained from tempeh producers in Java and Moluccas. 16S rRNA gene libraries and DNA sequencing were employed to analyze further the nature of bacterial diversity in two selected tempeh samples. The results of our study showed that different tempeh producer possessed different Bacterial ARISA (BARISA) or fungi ARISA (FARISA) profiles. However, BARISA profiles were found to be more discriminative than FARISA, and therefore BARISA would be more useful for tempeh genetic fingerprint or barcoding.